Non-pharmacological pain reliefing methods used during birth labour: An integrative research review (Research, Society and Development, 2021)
Childbirth always represented an important experience for most women. But it carries the myth of being painful, which makes cesarean to become the most frequent birth method. Humanized Childbirth is associated to the use of non-pharmacological methods, therefore, nursing play a fundamental role in promoting humanized birth. So, this study aims to carry out an integrative research review concerning non-pharmacological methods used to relief mother’s and baby’s pain at birth labor and, furthermore, to promote recommendations to professionals and mothers, based on scientific evidences. Using criteria for inclusion and exclusion the PICO strategy. The study shows that pain in labor is not restricted to the physiological process. It is also related to fear, tension, fatigue, cold, hunger, loneliness, among other factors, and the use of non-pharmacological methods had positive effects on the humanized delivery care, as they are safer, less invasive and provided pain relief. Professionals must be kept up-to-date on behalf of promoting changes at nursing procedures, helping childbirth to be as humanized as possible.